Novel anthropometric indices are superior adiposity indexes to portend visual impairment in middle-aged and older Chinese population - Qing Chen; Yanan Hou; Yifan Zhou; Jianfeng Luo; KaiweiSa Abuduxukuer; Chuchu Wang; Jialong Dong; Yiting Wang; Wenming Shi; Fei Shi; Qing Peng (BMJ Open Ophthalmology)
Objective To investigate differential associations of traditional and novel adiposity indices with visual impairment (VI) in the middle-aged and older Chinese population.Methods and analysis Based on the China Health and Retirement Longitudinal Study, 7750 Chinese older adults aged over 45 were included at baseline 2011, and 4133 participants who accomplished all three interviews from 2011 to 2015 were adapted for longitudinal analyses. We enrolled six adiposity indices, including the body mass index (BMI), waist-to-height ratio (WHtR), weight-adjusted-waist index (WWI), a body shape index (ABSI), body roundness index (BRI) and conicity index (ConI). Visual status and other covariates included sociodemographic characteristics, medical supports and lifestyle-related factors. Cross-sectional correlations were assessed using univariate and multivariate logistic regression analyses. For longitudinal analysis, generalised linear models with generalised estimating equations were used to determine the association between time-varying adiposity and visual status.Results Higher levels of WHtR/WWI/ABSI/BRI/ConI were significantly associated with an increased prevalence of VI, whereas a higher BMI was associated with a decreased prevalence of VI. Only WWI was significantly related to the prevalence of VI after adjustment for multiple confounders in both cross-sectional and longitudinal analyses (all p values <0.05). The multivariable-adjusted OR (95% CI) of VI associated with the highest (vs lowest) quintile of WWI was 1.900 (1.407 to 2.565).Conclusion WWI is a reliable alternative adiposity index that exhibits a dose–response association with the prevalence of VI in the Chinese population. The WWI-VI correlation may eliminate the obesity paradox in the ophthalmic epidemiological area and indicate the detrimental impact of changes in body composition on VI.